Innovative Approaches to Science Education: (Leveraging Technology and Inquiry-Based Learning to Enhance Student Engagement and Understanding) - Prof. Abdulqadir Obaidallah Alhomairi (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
Science education is undergoing a transformative shift, with educators increasingly embracing innovative approaches that leverage technology and inquiry-based learning to enhance student engagement, understanding, and achievement. This review paper explores the integration of technology and inquiry-based learning in science education, examining the impact of these approaches on student learning outcomes, as well as the challenges and opportunities they present. Through case studies, literature review, and analysis of current trends, we showcase successful implementations of technology-enhanced and inquiry-based learning approaches in diverse educational settings. Additionally, we discuss emerging technologies such as artificial intelligence, augmented reality, and data analytics, and their potential to revolutionize science education. Furthermore, we identify research gaps and offer recommendations for policymakers, educators, and institutions to support innovation and excellence in science education. By embracing innovation, addressing challenges, and fostering collaboration, we can create inclusive, engaging, and high-quality learning experiences that prepare students for success in an ever-changing world.